Deception as a Derived Function of Language - Oesch, Nathan (Frontiers in Psychology, 2016)
Language may be one of most important attributes which separates humans from other animal species. It has been suggested by some commentators that the primary biological function of human language is to deceive and selfishly manipulate social competitors. However, despite the existence of a large body of relevant theoretical and empirical literature in favour of the social bonding hypothesis for language function, the ostensible evidence and arguments for the deception hypothesis have not been fully discussed. The following review analyses the evidence and theoretical arguments from human social behavior, comparative animal behavior, and developmental psychology and suggests that deception shows clear signs of a derived function for language. Furthermore, in addition to being used relatively infrequently across most human and non-human animal contexts, deception appears to be utilized just as often for prosocial and social bonding functions, as it is for antisocial purposes. Future studies should focus on theoretical and experimental investigations which explore interactions between deceptive and honest language use in the context of social bonding.